2017
DOI: 10.1002/cphc.201700937
|View full text |Cite
|
Sign up to set email alerts
|

Mono‐ and Di‐Alkylation Processes of DNA Bases by Nitrogen Mustard Mechlorethamine

Abstract: The reactivity of nitrogen mustard mechlorethamine (mec) with purine bases towards formation of mono- (G-mec and A-mec) and dialkylated (AA-mec, GG-mec and AG-mec) adducts has been studied using density functional theory (DFT). To gain a complete overview of DNA-alkylation processes, direct chloride substitution and formation through activated aziridinium species were considered as possible reaction paths for adduct formation. Our results confirm that DNA alkylation by mec occurs via aziridine intermediates in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 48 publications
1
10
0
Order By: Relevance
“…Similar observations have been made for the aziridinium ion of mec when it was microhydrated with one to four water molecules. 36 For the most stable mono-, di-, and trihydrated complexes of SM, the C−Cl bonds involved in the H-bonding are extended by 0.01, 0.02, and 0.01 Å, respectively, at all four levels of theory. This bond is also lengthened in all other complexes where the C−Cl fragment is bound to water molecules by similar values.…”
Section: Computational Detailsmentioning
confidence: 95%
See 2 more Smart Citations
“…Similar observations have been made for the aziridinium ion of mec when it was microhydrated with one to four water molecules. 36 For the most stable mono-, di-, and trihydrated complexes of SM, the C−Cl bonds involved in the H-bonding are extended by 0.01, 0.02, and 0.01 Å, respectively, at all four levels of theory. This bond is also lengthened in all other complexes where the C−Cl fragment is bound to water molecules by similar values.…”
Section: Computational Detailsmentioning
confidence: 95%
“…33 The large difference in energy between SM-DNA adducts and SM•nH 2 O complies with in vivo experimental observations: SM tends to attack purine DNA bases in the aqueous cellular environment rather than undergo hydrolysis despite its instability in aqueous media after hydration. 12 Larranãga and co-workers 36 modeled the alkylation of DNA by aziridinium microhydrated with two water molecules and concluded that the presence of water in the hydration shells lowers the activation barrier for the aziridinium formation, which precedes the DNA alkylation reaction step. Further, the water present in the first hydration sphere of aziridinium then form H-bonds with the approaching DNA molecule, aiding in the S N 2 reaction.…”
Section: Computational Detailsmentioning
confidence: 99%
See 1 more Smart Citation
“…To answer these questions in the present paper we carry out a full QM investigation of the mechanism of α‐1,4‐glucan lyases including the final tautomerization process. This type of approach was already demonstrated to provide reliable results in the study of enzymatic mechanisms or biological/pharmaceutical processes . To this purpose, we use the M06‐2X functional and a QM model‐system built from the X‐ray crystal structure obtained by Rozeboom .…”
Section: Introductionmentioning
confidence: 99%
“…This type of approach was already demonstrated to provide reliable results in the study of enzymatic mechanisms or biological/pharmaceutical processes. [26][27][28][29][30][31][32][33][34][35] To this purpose, we use the M06-2X functional and a QM model-system built from the X-ray crystal structure obtained by Rozeboom. [22] This QM model-system (218 atoms) is rather large and includes all the aminoacidic residues that in principle can be responsible for important interactions.…”
Section: Introductionmentioning
confidence: 99%